An Analysis Of Communication Celebrity Endorsement On Brand Image - Inge Bunga Mira Dewi; Karina Amalia Anaway; Marlinda Irwanti Poernomo; Jamalullail Jamalullail; Son Wandrial (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The main objective of this study is to propose a conceptual model to assess whether persuasive messages can lead to acceptance in the form of information provided by Instagram social media opinion leaders, and, also, the extent to which messages on products and services affect brand image recommended by celebrity endorsement. Communication helps managers to do their jobs and responsibilities. Communication serves as the basis for planning. Celebrity endorsement are used as a common corporate communication strategy to build brand image. Advertisers believe that the use of celebrity endorsement affects advertising effectiveness as well as on purchase intention and repurchase. The study used a quantitative approach using 241 samples from clothing consumers using multiple linear regression processed with SPSS 25. The results of this study found that there was a significant and positive influence of celebrity endorsement on clothing companies brand image. Celebrity endorsement play an important role in improving clothing companies brand image with the endorsement method carried out by celebrity endorsement proven to be able to give a positive impression on the brand image in the eyes of consumers, especially on social media Instagram.